Crystallization of thermostable lipase from Geobacillus thermodenitrificans IBRL-nra - Anuradha Balan; Darah Ibrahim; Rashidah Abdul Rahim (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Crystallization of a protein is a process of formation of a solid crystal from a homogeneous solution which leads to the knowledge of its three dimensional structures and it plays important role in designing and engineering protein for specific purposes. Thermostable lipases are commercially significant for their potential use in industries as it is stable and active in organic solvents, possess a wide range of substrate specificity, resistance to high temperature and chemical denaturation. The purified thermostable lipase from Geobacillus thermodenitrificans IBRL-nra was screened for crystal formation using Hampton Research screening kit, HR2-121 and HR2-122 using hanging drop vapour diffusion and microbatch methods. Microcrystals and rod clusters grew from mixtures in formulation 14, 20, 21 and 38 of HR2-121 and formulation 14, 16, 32 and 45 of HR2-122. Further enhancement of the parameters was carried out for the formation of well-defined crystal. The parameters tested are pH (4.6, 6.5, 7.5 and 8.5) and concentration of CaCl2 (0.15-0.38M)